Left Atrial Decompression During Venoarterial Extracorporeal Membrane Oxygenation for Left Ventricular Failure in Children: Current Strategy and Clinical Outcomes. Issue 1 (30th September 2012) - Kotani, Yasuhiro; Chetan, Devin; Rodrigues, Warren; Sivarajan, V. Ben; Gruenwald, Colleen; Guerguerian, Anne‐Marie; Van Arsdell, Glen S.; Honjo, Osami
Abstract From 2005 to 2011, 23 of 178 (12.9%) patients with venoarterial (VA) extracorporeal membrane oxygenation (ECMO) had left atrial (LA) decompression to help improve left ventricular (LV) function, LA/LV dilatation, and/or lung edema. LA decompression was achieved with LA cannulation (n = 16), surgically created adjustable atrial septal defect (n = 3), or balloon atrial septostomy (n = 4). Sixteen (70%) patients had LA decompression at the time of ECMO initiation and all had LA decompression within 12 hours of ECMO initiation. ECMO duration was 5.9 ± 4.5 days and 16 (70%) patients were successfully decannulated. Subsequent intensive care unit and hospital survival was achieved in 13 (57%) and 12 (52%) patients, respectively. Earlier timing of LA decompression appeared to be associated with a high probability of weaning from ECMO and reasonable LV functional recovery.